Pembuatan Video Promosi Perpustakaan di Perpustakaan Universitas Islam Negeri Imam Bonjol Padang - Fitri, Dinni; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractIn this paper, it is discussed about Making Library Promotion Videos in Imam Bonjol State Islamic University Library Padang. The purpose of this paper is to describe the stages of making library promotional videos at the Imam Bonjol State Islamic University Library in Padang. This type of research is qualitative with descriptive method. Data collected through observation and interviews with the Head of Imam Bonjol State Islamic University Library Padang. Based on analyzing the data it can be concluded that the steps in making a library promotion video are follows: First, preproduction is the initial stage before the video production process consists of the discovery of ideas which are the theme of production, synopsis, treatment which gives an overview of the production theme, storyboards that describe a series of events, shooting scripts as a guide in the field, production planning, and production preparation. Second, production to realize all the steps in the preproduction stage. Third, post-production is the final stage in video production before it’s ready to be presented.Keywords: videos, promotions, libraries